2020
DOI: 10.3390/catal10020225
|View full text |Cite
|
Sign up to set email alerts
|

Supermagnetic Nano-Bifunctional Catalyst from Rice Husk: Synthesis, Characterization and Application for Conversion of Used Cooking Oil to Biodiesel

Abstract: The present work investigated the biodiesel production from used cooking oil catalyzed by nano-bifunctional supermagnetic heterogeneous catalysts (RHC/K2O/Fe) derived from rice husk doped with K2O and Fe synthesized by the wet impregnation method. The synthesized catalysts (RHC/K2O/Fe) were characterized for crystallinity by X-ray diffraction spectroscopy (XRD), total acidity and basicity using CO2/NH3-TPD, textural properties through Brunauer-Emmett-Teller (BET), thermal stability via thermogravimetric analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 86 publications
0
35
0
Order By: Relevance
“…As the pyrolysis temperature rose, a porous structure in the chars was formed due to the devolatilisation of PP plastic waste. In addition, the carbonisation of the polymer at elevated temperature also contributed to the increase in carbon content as well as improving the material porosity in the chars [49,50]. From our observations, when the temperature was increased from 450 to 600 • C, the pore size increased as the volatile matter were shattered, and the pores indicated the void spaces in chars [37].…”
Section: Surface Area and Porosity Measurementmentioning
confidence: 55%
“…As the pyrolysis temperature rose, a porous structure in the chars was formed due to the devolatilisation of PP plastic waste. In addition, the carbonisation of the polymer at elevated temperature also contributed to the increase in carbon content as well as improving the material porosity in the chars [49,50]. From our observations, when the temperature was increased from 450 to 600 • C, the pore size increased as the volatile matter were shattered, and the pores indicated the void spaces in chars [37].…”
Section: Surface Area and Porosity Measurementmentioning
confidence: 55%
“…5 International Journal of Polymer Science DW-Ni-400, DW-Ni-500, and DW-Ni-600 was lower than 7 Am 2 /kg. Since the Ms of the catalyst was higher than 7 Am 2 /kg, the magnetic separation of catalyst can be performed easily [36]; the VSM investigation of the catalysts indicated that DW-Ni-800 and DW-Ni-700 could be excellent MHC.…”
Section: Resultsmentioning
confidence: 99%
“…Purolite ® (PD206) is a commercial cation-exchange resin that is used to purify biodiesel by removing residual catalyst, water and other impurities, as well as acting as an adsorbent. A study conducted by Hazmi et al [9] used PD206 and BD10 dry ion-exchange resins (strong acid cation resins) to refine biodiesel derived from used cooking oil and rapeseed oil. Results showed that the resins had better removal for soap and glycerol; however, methanol removal was low and did not pass the biodiesel standard EN14214.…”
Section: Dry Washing By Ion-exchangementioning
confidence: 99%
“…Normall ferent fatty acids can be found in the triglycerides of vegetable oils and animal fat properties of the oils are influenced by the physical and chemical composition of th acids. Figure 1 shows the chemical reaction involved in the production of biodiese diesel has numerous advantages over petroleum diesel such as green, sustainabilit degradability and clean-burning fuel [9,10]. The use of low-grade oil as the feedstock could reduce the fuel quality.…”
Section: Introductionmentioning
confidence: 99%